South Korea's Perception Towards North Korea in Reunification Efforts during Moon Jae-In Administration: Image Theory - Darwan, Muhammad Rizky (Forum Ilmu Sosial, 2025)
South Korea’s foreign policy in its efforts toward reunification with North Korea is carried out through a peaceful and reconciliatory approach. The Panmunjom Declaration in 2018 marked a significant milestone in reviving peace efforts on the Korean Peninsula. The series of subsequent events reflected a positive perception of one another between the two countries. This study will examine how South Korea has constructed its image of North Korea through the Panmunjom Declaration, as part of its efforts to pursue peace and reunification on the Korean Peninsula. The declaration was followed by several high-level meetings between national leaders, which were expected to lead to positive outcomes. However, by the end of President Moon Jae-in’s term, these efforts toward peace and unity had not been achieved. This research employs Image Theory to examine how South Korea built its image of North Korea. Image Theory will be analyzed using a qualitative method. Both primary and secondary data will be examined through triangulation and causal process tracing (CPT). CPT will be applied to trace the causal mechanisms of policies and political decisions during Moon Jae-in’s administration, and to understand how these sequences of events shaped or altered South Korea’s perceptions of North Korea. This study argues that while South Korea perceives North Korea as a partner or ally, North Korea’s nuclear program continues to be viewed as a threat.